Serum Lipopolysaccharide‐Binding Protein Levels and the Incidence of Cardiovascular Disease in a General Japanese Population: The Hisayama Study - Masako Asada; Emi Oishi; Satoko Sakata; Jun Hata; Daigo Yoshida; Takanori Honda; Yoshihiko Furuta; Mao Shibata; Kosuke Suzuki; Hiroshi Watanabe; Norihito Murayama; Takanari Kitazono; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Epidemiological studies have reported a link between serum LBP (lipopolysaccharide‐binding protein) levels and lifestyle‐related diseases. However, there have been no longitudinal studies investigating the association of serum LBP levels and the incidence of cardiovascular disease (CVD) in general populations. Methods and Results A total of 2568 community‐dwelling Japanese individuals 40 years and older without prior CVD were followed for 10 years (2002–2012). Serum LBP levels were divided into quartiles (quartile 1: 2.20–9.68 μg/mL; quartile 2: 9.69–10.93 μg/mL; quartile 3: 10.94–12.40 μg/mL; quartile 4: 12.41–24.34 μg/mL). The hazard ratios (HRs) and their 95% CIs for the incidence of CVD were computed using a Cox proportional hazards model. During the follow‐up period, 180 individuals developed CVD. The age‐ and sex‐adjusted cumulative incidence of CVD increased significantly with higher serum LBP levels (P for trend=0.005). Individuals with higher serum LBP levels had a significantly greater risk of the development of CVD after adjusting for conventional cardiovascular risk factors (quartile 1: HR, 1.00 [reference]; quartile 2: HR, 1.04 [95% CI, 0.60–1.78]; quartile 3: HR, 1.52 [95% CI, 0.92–2.51]; and quartile 4: HR, 1.90 [95% CI, 1.17–3.09]; P for trend=0.01). This association remained significant after additional adjustment for homeostasis model assessment of insulin resistance (P for trend=0.01). However, when additional adjustment was made for high‐sensitivity C‐reactive protein, the association was attenuated to the nonsignificant level (P for trend=0.08). Conclusions The present findings suggest that higher serum LBP levels are associated with increased risk of the development of CVD in the general Japanese population. Low‐grade endotoxemia may contribute to the pathogenesis of CVD through chronic systemic inflammation.